Modern Climate and Soil Properties Explain Functional Structure Better Than Phylogenetic Structure of Plant Communities in Northern China - Shi, Yabo; Su, Chuang; Wang, Mingchen; Liu, Xinliang; Liang, Cunzhu; Zhao, Liqing; Zhang, Xinyu; Minggagud, Hugjiltu; Feng, Gang; Ma, Wenhong (Frontiers in Ecology and Evolution, 2020)
Examination of the mechanisms of the plant community assembly at a geographical scale is an interesting topic in ecology and biogeography, which are of great significance for the understanding of species coexistence and biodiversity conservation. But so far, only a few studies have simultaneously assessed the relative roles of multiple-scale factors in shaping the phylogenetic and functional structure of plant communities at a macroecological scale. In this study, we linked modern climate, glacial-interglacial climate change, and soil properties with the phylogenetic and functional structure of shrub and herbaceous plant communities in Inner Mongolia, China, an arid and semi-arid region. Our results showed that the functional structure of plant communities was more associated with modern climate and soil properties than the phylogenetic structure, especially for the soil properties. Modern precipitation was found in all the combinations of variables that were most closely related to the community structure in this arid and semi-arid region. These findings suggest that the phylogenetic and functional structure of biotic communities may be affected by processes at divergent spatial-temporal scales. That is, the functional structure is better linked with the modern and local factors while the phylogenetic structure is more associated with the historical and regional processes. This study highlights the importance of the associations between the different biodiversity dimensions and divergent drivers.